Pelatihan Pemeliharaan dan Perbaikan Motor Listrik - Rakhmad Syafutra Lubis; Ramdhan Halid Siregar; Syukriyadin Syukriyadin; Alfisyahrin Alfisyahrin; Saifuddin Muhammad Jalil (Indo Publishing, 2026)
Electric motors are widely used in various places to assist human work. Their intensive use makes damage due to age and operating conditions a common occurrence. The most frequent damage occurs in the motor windings, the most critical part that generates a rotating magnetic field. Repairing this damage requires rewinding the coils with high precision, as errors can cause the motor to malfunction. To extend the motor's service life and reduce repair costs, skilled personnel are needed in the community who can perform electric motor maintenance and repair. Therefore, the community service team conducted training on motor winding rewinding for interested community members. This training utilized experts from the Department of Electrical and Computer Engineering, Faculty of Engineering, Syiah Kuala University, including lecturers, students, and laboratory staff. This activity aims to increase the number of skilled workers in electric motor maintenance and repair, particularly in rewinding coils, so that electric motors can function properly again and maintenance cost savings can be improved in the community. The results achieved showed a noticeable improvement in participants' understanding after the training, and participants were able to perform the motor winding rewinding practice under guidance.